Role of thalassemia screening in prevention and control of thalassemia - a 5 year experience - Mendiratta, Suman Lata; Mittal, Meenakshi; Naaz, Farha; Singh, Sompal; Anand, Smriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thalassemia is a commonest genetic blood disorder in India which can be prevented by antenatal screening and prenatal diagnosis. Aim of the study was to screen antenatal women and their spouses to detect “couples at risk” of thalassemia major births and offering them genetic counseling and option of prenatal diagnosis thereby preventing the birth of thalassemia major babies. Methods: Thalassemia screening for antenatal women was done by NESTROFT test and RBC Indices (MCV, MCH, and RBC count). Confirmation of diagnosis was done by HPLC test. Husbands of women testing positive on HPLC were also tested and couples at risk detected. They were counseled and referred for prenatal genetic diagnosis. Women carrying thalassemia major fetus were advised termination and those with normal and thalassemia minor fetus were advised to continue pregnancy. Results: A total of 93871 patients were screened and HPLC was done on 10983 patients. 7.07% had one or the other hemoglobinopathies and 5.8% had beta thalassemia trait. Among antenatal beta thalassemia trait was found in 5.02%, HbD in 0.36%, HbE in 0.58% and HbS 0.05%. Forty two “at risk couples” (both husband and wife thalassemia trait) were identified, 16 of these underwent prenatal diagnosis and 3 thalassemia major births were terminated. Conclusions: Lack of awareness, late registration, husbands not coming/turning up for their test and “at risk couples” opting out of prenatal diagnosis are the cause of thalassemia major births which can be prevented if awareness is generated amongst masses, screening and prenatal genetic diagnosis services are made widely available.